Osteosarcoma of the ulna with pulmonary metastasis in Agapornis roseicollis - Suzuki, Felipe Sueo de Freitas [UNESP]; Penteado, Kaio Henrique de Lariva [UNESP]; Pádua, Daniela [UNESP]; Andrade, Alexandre [UNESP]; Machado, Gisele [UNESP]; Garcia, Sérgio [UNESP]; Pinoti, Luciana [UNESP]; Senhorello, Igor Luiz [UNESP] (National Library of Serbia, 2025)
Osteosarcoma (OSA) is a malignant bone neoplasm of mesenchymal origin characterized by the proliferation of osteoblasts, being considered rare in birds. This paper discusses a rare occurrence of osteosarcoma in a wing with pulmonary metastasis in a Agapornis roseicollis, with a history of prostration and a drooping left wing for two days. Radiographic examination revealed findings indicative of an aggressive bone lesion in the proximal third of the left ulna, and signs of a pathological fracture in the ipsilateral radius. Additionally, a focal nodular lesion was identified in the left pulmonary field within the coelomic cavity. Cytological examination of the wing neoformation revealed signs of infiltrative, non-encapsulated malignant neoplastic proliferation of osteoblasts, consistent with a malignant mesenchymal neoplasm. Three days later, the patient died, and post-mortem and histopathological examinations of the lesions were consistent with OSA in the wing associated with pulmonary metastasis. Due to the scarcity of data regarding this theme, the present report could be useful for veterinarians.